Risk factors for prostate cancer: A case control study - Hamid Shafi; Mouloud Agajani Delavar; Reza Maghsoudi (Babol University of Medical Sciences, 2016)
Introduction: Prostate cancer is the second leading cause of cancer-related death in men. The aim of this study was to examine the association between prostate cancer and possible etiological agents. Methods: In case-control study 60 men aged 40-65 years from March 2013 and May 2016, with prostate cancer were studied. For each prostate cancer case, there were one control, who were matched in terms of age and residence. The demographic factors of men with prostate cancer were compared with healthy cases as a control group. Results: After adjusting the variables, the obesity (BMI ≥ 25) (OR= 16.07, 95% CI= 4.90-52.67), the sitting height ≥ 111 (OR= 6.45, 95% CI= 1.87-22.23), current use hookah (OR= 1.84, 95% CI= 0.48-7.03), and the positive family history of prostate cancer (OR= 55.60, 95% CI= 9.04-341.93) were found to be associated with an increased risk of prostate cancer. Conclusion: To decrease the prostate cancer among Iranian men emphasis should be placed on screening program to identify prostate cancer in men with the positive family history of cancer, the overweight one, higher sitting height and those who use hookah.